Production of English Consonants: Bilabial Voiced /P/ and the Voiced Labiodental Fricative /V/ by Saudi ESL/EFL Students - Alharbi, Samar (Advances in Social Sciences Research Journal, 2022)
The language systems and the production of letter sounds seem to be different among people who speak different languages. Non-native speakers of English have some variations in language production and sound when they speak English due to the differences between the native language and the target language. This paper explores the issues related to the absence of the bilabial stop /p/ and the voiced labiodental fricative /v/ in Arabic speakers. It also presents some recommendations to overcome pronunciation problems.